2019
DOI: 10.18393/ejss.552563
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biological soil quality indicators under saline soil condition after amelioration with alfalfa (Medicago sativa L.) cultivation in meadow Solonchak

Abstract: Land use and amelioration practices are considered as main drivers in change of biological soil quality indicators in meadow Solonchaks. To gain insight into the impact of amelioration with alfalfa (Medicago sativa L.) cultivation on the underlying soil microbiological and biochemical properties, the objective of this study was to determine the effect of alfalfa (Medicago sativa L.) cultivation on biological soil quality indicators such as microorganisms counts, microbial biomass, basal soil respiration and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Between 2017 and 2020, the difference in seed yield and dry hay of alfalfa between unfertilized plots (T1) and fertilized plots (T4, T5) further increased, and a significant difference was observed between the T1 and T4 treatments (Figure 3). These findings corroborated the results of other studies that reported a positive influence of P and N on alfalfa yield even in soils (Markus and Battle, 1965;Kafkafi et al, 1977;Barbarick, 1985;Macolino et al, 2013;Yertayeva et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…Between 2017 and 2020, the difference in seed yield and dry hay of alfalfa between unfertilized plots (T1) and fertilized plots (T4, T5) further increased, and a significant difference was observed between the T1 and T4 treatments (Figure 3). These findings corroborated the results of other studies that reported a positive influence of P and N on alfalfa yield even in soils (Markus and Battle, 1965;Kafkafi et al, 1977;Barbarick, 1985;Macolino et al, 2013;Yertayeva et al, 2019).…”
Section: Resultssupporting
confidence: 92%
“…A close dependence of the content of mobile phosphorus on the amount of excrement was found in August (r = 0.75). Bioindicators are often used as sensitive indicators of soil fertility under different land use systems and the degree of its degradation due to anthropogenic factors (Schwilch et al, 2016;Bünemann et al, 2018;Yertayeva et al, 2019). Biological diagnostics of soils is an important component of both local and global monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…Saline-sodic soils are found across various continents, ranging from tropical to polar zones, but they are most common in the Northern Hemisphere. In the Commonwealth of Independent States (CIS), the area covered by saline-sodic soils amounts to 120 million hectares, and the escalating expansion of these soils has made their reclamation a prominent concern in modern soil science (Yertayeva et al, 2019). Kazakhstan, a country located mostly within the largest drainless part of the plain, faces an uneven distribution of saline soils.…”
Section: Introductionmentioning
confidence: 99%
“…Crop losses due to sodic salinity in these areas range from 15% to 45% (Funakawa et al, 2000;Saparov, 2014;Pachikin et al, 2014;Otarov, 2014;Laiskhanov et al, 2016;Suska-Malawska et al, 2019;Zhang et al, 2019;Ma et al, 2019;Yertayeva et al, 2019;Kussainova et al, 2020;Liu et al, 2022;Suska-Malawska et al, 2022). Peasant farms annually apply various agricultural practices, from plowing to harvesting, to address salinesodic soil patches.…”
Section: Introductionmentioning
confidence: 99%